2017
DOI: 10.1007/s13595-017-0647-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil preparation methods and plant types on the establishment of poplars on forest land

Abstract: & Key message The success of poplar plantations on forest land was affected by soil preparation, plant type, site, and clone. Mounding in combination with large plant types (rooted plants or long cuttings) of site-adapted clones achieved the highest survival and growth. & Context Poplars (Populus species and hybrids) are fastgrowing trees used to make various products. In north European countries, they are mainly grown on agricultural land, but interest in planting poplars on forest land has increased. & Aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The other study investigated the effect of different site preparation methods on establishment success on forest land. Similar studies have previously been carried out and published for poplars (Hjelm and Rytter 2016;Mc Carthy et al 2017).…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…The other study investigated the effect of different site preparation methods on establishment success on forest land. Similar studies have previously been carried out and published for poplars (Hjelm and Rytter 2016;Mc Carthy et al 2017).…”
Section: Introductionsupporting
confidence: 78%
“…Mounding, on the other hand, was one of the best methods. The result is probably a combined effect of higher soil temperature (Örlander et al 1990;Vapaavuori et al 1992), less risk for waterlogged conditions (Mc Carthy et al 2017) and reduced competition from vegetation (Nilsson and Örlander 1995;Bilodeau-Gauthier et al 2011;Johansson et al 2013). The low growth in the patch scarification was considered an effect of planting spots below soil surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phillips et al ( 2014 ) found that 3 m poles produced more biomass and had the best root spread and root length compared to 1 m wands and 0.5 m stakes of poplar and willow. Mc Carthy et al ( 2017 ) found that rooted plants and long cuttings (50 cm) of poplar performed better than short cuttings (20 cm) on forest land, and especially in combination with mounding. In the present study, the same plant material was used, but on agricultural land that is different from forest land both regarding soil characteristics and the methods that could be used for site preparation.…”
Section: Discussionmentioning
confidence: 99%
“…A lot of research deals with different land preparation methods in the world. Most of them come from northern Europe and North America (Makitalo, 1999;Archibold et al, 1999;McCarthy et al, 2017), where the climatic and edaphic conditions greatly differ from the conditions existing in Mediterranean areas (e.g. very low temperatures, wet soil conditions).…”
Section: Introductionmentioning
confidence: 99%